Robustness and Vulnerability of the Autoregulatory System That Maintains Nuclear TDP-43 Levels: A Trade-off Hypothesis for ALS Pathology Based on in Silico Data - Sugai, Akihiro; Kato, Taisuke; Koyama, Akihide; Koike, Yuka; Kasahara, Sou; Konno, Takuya; Ishihara, Tomohiko; Onodera, Osamu (Frontiers in Neuroscience, 2018)
Abnormal accumulation of TAR DNA-binding protein 43 (TDP-43) in the cytoplasm and its disappearance from the nucleus are pathological features of amyotrophic lateral sclerosis and frontotemporal dementia (ALS/FTD) and are directly involved in the pathogenesis of these conditions. TDP-43 is an essential nuclear protein that readily aggregates in a concentration-dependent manner. Therefore, cells must strictly maintain an appropriate amount of nuclear TDP-43. In one relevant maintenance mechanism, TDP-43 binds to its pre-mRNA and promotes alternative splicing, resulting in mRNA degradation via nonsense-mediated mRNA decay. The level of nuclear TDP-43 is tightly regulated by these mechanisms, which control the amount of mRNA that may be translated. Based on the results of previous experiments, we developed an in silico model that mimics the intracellular dynamics of TDP-43 and examined TDP-43 metabolism under various conditions. We discovered an inherent trade-off in this mechanism between transcriptional redundancy, which maintains the robustness of TDP-43 metabolism, and vulnerability to specific interfering factors. These factors include an increased tendency of TDP-43 to aggregate, impaired nuclear-cytoplasmic TDP-43 transport, and a decreased efficiency of degrading abnormal proteins, all of which are functional abnormalities related to the gene that causes familial ALS/FTD. When these conditions continue at a certain intensity, the vulnerability of the autoregulatory machinery becomes apparent over time, and transcriptional redundancy enters a vicious cycle that ultimately results in TDP-43 pathology. The results obtained using this in silico model reveal the difference in TDP-43 metabolism between normal and disease states. Furthermore, using this model, we simulated the effect of a decrease in TDP-43 transcription and found that this decrease improved TDP-43 pathology and suppressed the abnormal propagation of TDP-43. Therefore, we propose a potential therapeutic strategy to suppress transcriptional redundancy, which is the driving force of the pathological condition caused by the specific factors described above, in patients with ALS presenting with TDP-43 pathology. An ALS animal model exhibiting TDP-43 pathology without overexpression of exogenous TDP-43 should be developed to investigate the effect of alleviating the transcriptional redundancy of TARDBP.